2010
DOI: 10.1074/jbc.m110.178707
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Low Molecular Weight Pyroglutamate Aβ Oligomers in Alzheimer Disease

Abstract: N-terminally truncated A␤ peptides starting with pyroglutamate (A␤pE3) represent a major fraction of all A␤ peptides in the brain of Alzheimer disease (AD) patients. A␤pE3 has a higher aggregation propensity and stability and shows increased toxicity compared with full-length A␤. In the present work, we generated a novel monoclonal antibody (9D5) that selectively recognizes oligomeric assemblies of A␤pE3 and studied the potential involvement of oligomeric A␤pE3 in vivo using transgenic mouse models as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
128
4
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(153 citation statements)
references
References 50 publications
13
128
4
8
Order By: Relevance
“…Previous studies reported that 3-month-old APP/PS1 mice exhibit anxiety-like phenotype, although without spatial cognitive dysfunction, when compared with age-matched WT controls (Trinchese et al 2004;Webster et al 2014). The open field and elevated plus maze test confirmed that anxietylike behaviors continue to exist in the late stages of this mouse AD model, similar to the Tg2576 (Gil-Bea et al 2007;Lassalle et al 2008), J20 (Harris et al 2010;Cissé et al 2011), and 5xFAD mice (Wirths et al 2010;Shukla et al 2013), all of which also exhibit anxietyrelated behavior deficits in the elevated plus maze task. However, there is no anxiety-related behavior abnormality in the APP/PS1 double knock-in mice from 7 to 24 months old (Webster et al 2013); while 3xFAD mice show decreased anxiety-related behavior in the open field and elevated plus maze test (Nelson et al 2007;Filali et al 2012).…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies reported that 3-month-old APP/PS1 mice exhibit anxiety-like phenotype, although without spatial cognitive dysfunction, when compared with age-matched WT controls (Trinchese et al 2004;Webster et al 2014). The open field and elevated plus maze test confirmed that anxietylike behaviors continue to exist in the late stages of this mouse AD model, similar to the Tg2576 (Gil-Bea et al 2007;Lassalle et al 2008), J20 (Harris et al 2010;Cissé et al 2011), and 5xFAD mice (Wirths et al 2010;Shukla et al 2013), all of which also exhibit anxietyrelated behavior deficits in the elevated plus maze task. However, there is no anxiety-related behavior abnormality in the APP/PS1 double knock-in mice from 7 to 24 months old (Webster et al 2013); while 3xFAD mice show decreased anxiety-related behavior in the open field and elevated plus maze test (Nelson et al 2007;Filali et al 2012).…”
Section: Discussionsupporting
confidence: 62%
“…In addition, the titer of IgM autoantibodies against A␤ pE3 correlated with the cognitive status of individuals at risk to develop AD (96). In good agreement, the level of A␤ pE3 oligomers was significantly decreased in the plasma of AD patients (51). However, it is noteworthy that these studies are pilot studies with small group sizes and need to be further replicated and confirmed using larger cohorts of patients and controls.…”
Section: Pyroglutamate As a Potential Diagnostic Markermentioning
confidence: 68%
“…A recently generated novel monoclonal antibody (9D5) was used to demonstrate that it is possible to detect low molecular weight pyroglutamate-modified A␤ oligomers (51). The selectivity of the antibody for low molecular weight (4 -10-mers) pyroglutamate-modified A␤ was confirmed by size exclusion chromatography and immunoblot assays.…”
Section: Passive Immunization Against Low Molecular Weight Pyroglutammentioning
confidence: 99%
See 1 more Smart Citation
“…However, it cannot be excluded that the unmodified A␤ 3-42 also participates in the observed deficits. It should be noted that passive immunization against low molecular weight pyrogutamate-modified A␤ oligomers produces beneficial therapeutic effects in 5XFAD mice (39). These data imply that a change in the amount of A␤ pE3 is sufficient to affect pathology despite the presence of other A␤ isotypes.…”
Section: Discussionmentioning
confidence: 92%